Improving Queuing Culture through the Train Game Method for 5-6 Year Old Children at RA Muslimat NU Pretek - Mariah (Jurnal Pendidikan Profesi Guru, 2025)
This study aims to improve the fine motor skills of children aged 5-6 years through collage activities with various media at RA Muslimat NU Pretek, Pecalungan District, Batang Regency. This study uses the Classroom Action Research (PTK) method with a quantitative descriptive approach which is carried out in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were 47 children, consisting of 28 boys and 19 girls. The focus of the research includes the steps of teachers in the implementation of collage activities, such as planning drawing patterns, introducing tools and materials, and evaluating children's work. Inhibiting and supporting factors of collage activities were identified through observation and interviews with teachers. The results of the study show that the application of collage activities through scissors and gluing activities can significantly improve children's fine motor skills. This can be seen from the increase in pre-cycle results by 6%, increasing to 36% in cycle I, and reaching 78% in cycle II. Thus, collage activities have proven to be effective in developing fine motor skills in early childhood through a fun and meaningful learning process.